Development of CRISPR/Cas9 Construct in Rice (Oryza sativa subsp. indica) Using Golden Gate Cloning Method Towards Drought Tolerance: Development of CRISPR/Cas9 Construct in Rice (Oryza sativa subsp. indica) Using Golden Gate Cloning Method Towards Drought Tolerance - Nurul Hidayah Samsulrizal; Anis Afuza Md Yusof; Amin-Asyraf Tamizi; Nurul Asyikin Mohd Zim; Siti Syafiqa Abdul Sattar; Mohd Syahmi Salleh; Nur Sabrina Ahmad Azmi; Zamri Zainal; Zarina Zainuddin (Journal of Tropical Life Science, 2023)
Rice (Oryza sativa) is a staple food consumed by the majority of the world’s population. Climate change, however, has created a significant threat to our food security as it posed severe effects on rice production. The emergence of genome editing technology has opened a new era in crop improvement. Hence, this study aims to develop the CRISPR/Cas9 construct of drought tolerance for O. sativa subsp. indica cv. IR64 using Golden Gate cloning method. For this purpose, the generation of CRISPR/Cas9 constructs involved several stages, i.e., characterization of SUMO E2-Conjugating Enzyme (OsSCE1) gene, single-guide RNA (sgRNA) design and vector construction. FGENESH, GeneMarkS, InterProScan, and Blast2GO programmes – were used for the OsSCE1 gene characterisation. The putative OsSCE1 gene isolated from IR64 was then verified by sequencing, and the gene was 585 bp long and showed 99% identity with O. sativa on chromosome 10. In silico analysis concluded the gene is involved in abiotic stress regulation. The 20 bp sgRNA was designed manually with the aid of gRNA prediction programmes including CCTop, and Benchling. The virtual vector was validated using the Golden Gate Cloning approach and later confirmed through sequencing. The assembly involved separate vectors containing the OsSCE1 sgRNA sequence, plant selectable marker, and Cas9 cassette to construct standardised elements for hierarchical modular cloning (MoClo). This study demonstrated that our format, as the gene insertion are achievable, resulting in a speedier and more efficient assembly process which may contribute to improve drought tolerance in indica rice. Further study on the Agrobacterium-mediated transformation using the developed construct may be conducted to determine the efficacy of knocking out candidate genes in improving drought tolerance ability O. sativa